1997
DOI: 10.1111/j.1524-4725.1997.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycolic Acid Peels in the Treatment of Melasma among Asian Women

Abstract: A cream containing 10% glycolic acid and 2% hydroquinone (Neostrata AHA Age Spot and Skin Lightening Gel) improved melasma and fine facial wrinkling in Asian women. In combination with glycolic acid peels at 3-week intervals the lightening of melasma is subjectively much better. This improvement does not reach statistical significance and the sample size is small (n = 10).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 3 publications
3
65
0
2
Order By: Relevance
“…Sarkar et al (2002) have demonstrated that serial glycolic acid peels can significantly improve the clinical efficacy of a modified Kligman's formula. Improvement of pigmented spots has been observed in Asian women treated with daily application of 10% glycolic acid and 2% hydroquinone in association with 70% glycolic acid peels every 3 weeks (Lim and Than, 1997).…”
Section: Combination Therapiesmentioning
confidence: 96%
“…Sarkar et al (2002) have demonstrated that serial glycolic acid peels can significantly improve the clinical efficacy of a modified Kligman's formula. Improvement of pigmented spots has been observed in Asian women treated with daily application of 10% glycolic acid and 2% hydroquinone in association with 70% glycolic acid peels every 3 weeks (Lim and Than, 1997).…”
Section: Combination Therapiesmentioning
confidence: 96%
“…Glycolic acid (GA) peel, an AHA, has been widely used for pigmentary dyschromias and acne, [3][4][5][6][7][8] but few studies have evaluated GA peels in dark skins, including Asian patients. 9 Salicylic-mandelic acid peel (SMP) is a newer combination peel that combines the properties of a BHA and an AHA.…”
mentioning
confidence: 99%
“…Since Kligman et al [10] reported that the combined use of topical atRA, dexamethasone, and hydroquinone was more effective as a depigmenting formulation than a single use of each reagent, hydroquinone has been widely used in combination with atRA and corticosteroid [4,18]. Furthermore, in recent years, hydroquinone has been used in combination with laser therapies [1,2,8], dermabrasion [20], and chemical peelings such as Jessner's solution and glycolic acid [3,5,13,14]. Although Kligman's mixture is well-known and widely used, the bleaching ability is weak and a prolonged period of treatment is required, with variable clinical results.…”
mentioning
confidence: 99%